Hyperhomocysteinemia in Tunisian bipolar I patients - Ezzaher, Asma; Mouhamed, Dhouha Haj; Mechri, Anwar; Omezzine, Asma; Neffati, Fadoua; Douki, Wahiba; Bouslama, Ali; Gaha, Lotfi; Najjar, Mohamed Fadhel (Psychiatry and clinical neurosciences, 2011)
Aims:  The aim of the present study was to investigate hyperhomocysteinemia in Tunisian bipolar I patients according to 5,10‐methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism. Methods:  The subjects consisted of 92 patients with bipolar I disorder diagnosed according to DSM‐IV, and 170 controls. Plasma total homocysteine, folate and vitamin B12 were measured. MTHFR C677T polymorphism was determined by polymerase chain reaction–restriction fragment length polymorphism. Results:  Compared with controls, patients had a significantly higher homocysteine level (16.4 ± 9.8 vs 9.6 ± 4.5 µmol/L; P < 0.001) and a significantly lower folate level (3.2 ± 0.9 vs 6.5 ± 3.2 µg/L; P < 0.001). C677T MTHFR polymorphism genotype frequencies were in Hardy–Weinberg equilibrium. After adjustment for MTHFR C677T genotypes, hypofolatemia, hypovitamin B12 and for potential confounding factors, the odds ratio (OR) of hyperhomocysteinemia associated with bipolar disorder remained significant (OR, 5.53; 95% confidence interval: 1.92–15.86; P = 0.001). In patients, there was no significant change in hyperhomocysteinemia, hypofolatemia and hypovitamin B12 with regard to the clinical and therapeutic characteristics, whereas the highest prevalence of hyperhomocysteinemia was found in depressive patients and when illness duration was >12 years. Hypofolatemia was seen in all patients on lithium and in the majority of patients on carbamazepine, and the highest prevalence of hypovitamin B12 was noted in patients taking carbamazepine. Conclusion:  Hyperhomocysteinemia was more frequent in bipolar I patients independent of C677T polymorphism. Patients had reduced levels of folate, which modulates homocysteine metabolism. Indeed, this finding indicates that folate supplementation may be appropriate for bipolar patients with hyperhomocysteinemia.